2009
DOI: 10.1007/s12404-009-0109-6
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and simulation of strata movement for protective seam mining with large interburden

Abstract: Based on simulated material scale modeling and numerical simulation, the protective seam mining method was conducted at one coal mine. After extracting the No.15 seam, the overlying strata movement and the deformation of the No.9-10 protected seam were studied. The experiment results show that it is feasible to destress the protected seams with large interburden thickness. When the face had advanced 200 m from the setup room, the No.9-10 seam was fully destressed, resulting in easy gas drainage in the destress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Thakur 26 pointed out that the gas emission space might extend to 270 ft (82.3 m) below and 1000 ft (304.8 m) above the mining coal seam, which laid the foundation for the remote protection of coal seam mining. Song et al 27 and Liu et al 28 discussed the possibility of remotely protected coal seam mining (layer spacing of 150 and 129 m, respectively) based on modeling and numerical simulation of simulated material scale. The follow‐up field studied by Liu et al 29 confirmed that under specific geological conditions, the long‐distance protective layer could also obtain sufficient decompression effect.…”
Section: Introductionmentioning
confidence: 99%
“…Thakur 26 pointed out that the gas emission space might extend to 270 ft (82.3 m) below and 1000 ft (304.8 m) above the mining coal seam, which laid the foundation for the remote protection of coal seam mining. Song et al 27 and Liu et al 28 discussed the possibility of remotely protected coal seam mining (layer spacing of 150 and 129 m, respectively) based on modeling and numerical simulation of simulated material scale. The follow‐up field studied by Liu et al 29 confirmed that under specific geological conditions, the long‐distance protective layer could also obtain sufficient decompression effect.…”
Section: Introductionmentioning
confidence: 99%
“…Thakur (2006) indicated that the gas emission space may extend to 270 ft (82.3 m) below the coal seam being mined and 1000 ft (304.8 m) above it, which laid the foundation of remote protective seam mining. Song et al (2009) andLiu et al (2010) discussed the possibility of remote protected seam mining (layer spacing: 150 m and 129 m respectively) based on simulated material scale modeling and numerical simulation. The follow-up field studies from Liu et al (2013) confirmed that under certain geological situation it is feasible for the protected seams to get sufficient pressure-relief effects even under such a long distance.…”
Section: Introductionmentioning
confidence: 99%